THE INFLUENCE OF FINTECH ON RURAL TEENAGERS’ CONSUMPTIVE BEHAVIOR WITH DIGITAL LIFESTYLE AS INTERVENING - Efendi, Muhammad Rahul; Gerhani, Febrina; Prasetyorini, Pudhak (STKIP Persada Khatulistiwa Sintang, 2025)
This research explores the impact of Financial Technology (Fintech) on the consumptive behavior of teenagers in rural areas, specifically in Desa Cumedak, Kecamatan Sumberjambe, Kabupaten Jember. The study is motivated by the increasing use of digital financial services among adolescents, facilitated by easy access through e-wallets and paylater features. This study used a quantitative approach. The research method used was a survey. The sample included 110 respondents aged 15 to 24.. Data were analyzed both descriptively and inferentially using path analysis to examine the direct and indirect effects of Fintech usage, with digital lifestyle as an intervening variable and financial literacy as a moderating variable. The findings indicate that frequent use of Fintech correlates with a higher tendency toward impulsive and unplanned consumption among rural teenagers. The study implies the need to integrate digital financial literacy into school curricula and youth empowerment programs at the community level.